Placental Location Affects Cesarean Complications in Patients with Placenta Previa - Dogan Durdag, Gulsen; Kalayci, Hakan; Yilmaz Baran, Safak; Yuksel Simsek, Seda; Alemdaroglu, Songul; Ozdogan, Serdinc; Bulgan Kilicdag, Esra (Gynecology Obstetrics & Reproductive Medicine, 2021)
Objective: Placenta previa may cause massive hemorrhage at antenatal, intrapartum or postpartum periods and is one of the leading causes of maternal morbidity and mortality. Anterior or posterior location of placenta previa can change cesarean technique and management of the operation. Aim of this study is to assess factors increasing intraoperative complications in patients with placenta previa and investigate the significance of anterior placenta location apart from other factors. Study Design: This is a retrospective cohort study which was conducted in one center including 83 patients followed with placenta previa in three years’ duration. Placental location, presence, and depth of myometrial invasion, previous uterine surgery and the type of uterine incision were evaluated. Intraoperative hemorrhage, need for blood transfusion and hysterectomy, complete blood count parameters of mother and newborn were compared between the anterior and posterior placenta previa. Results: Previous uterine surgery, abnormally invasive placenta and need for blood transfusion were significantly higher in patients with anterior placenta previa. The increasing number of previous cesarean operations enhanced placental invasion to cesarean scar area in anterior placentation, leading to higher rates of blood transfusion, classical incision, and hysterectomy. Also, when the patients with previous cesarean or classical incision were excluded, anterior placentation differed significantly when compared with posterior placentation with respect to hemoglobin differences between preoperative and postoperative values. Conclusion: Anterior location of placenta previa increases hemorrhagic complications. Placental location, presence, and depth of invasion should be assessed and timing of delivery should be planned with appropriate preparation of blood products before delivery.